Drug resistance phenotypes and genotypes in Mexico in representative gram-negative species: Results from the infivar network. - Elvira Garza-González; Paola Bocanegra-Ibarias; Miriam Bobadilla-Del-Valle; Luis Alfredo Ponce-de-León-Garduño; Verónica Esteban-Kenel; Jesus Silva-Sánchez; Ulises Garza-Ramos; Humberto Barrios-Camacho; Luis Esaú López-Jácome; Claudia A Colin-Castro; Rafael Franco-Cendejas; Samantha Flores-Treviño; et al. (PLoS ONE)
Aim This report presents phenotypic and genetic data on the prevalence and characteristics of extended-spectrum β-lactamases (ESBLs) and representative carbapenemases-producing Gram-negative species in Mexico. Material and methods A total of 52 centers participated, 43 hospital-based laboratories and 9 external laboratories. The distribution of antimicrobial resistance data for Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae complex, Acinetobacter baumannii complex, and Pseudomonas aeruginosa in selected clinical specimens from January 1 to March 31, 2020 was analyzed using the WHONET 5.6 platform. The following clinical isolates recovered from selected specimens were included: carbapenem-resistant Enterobacteriaceae, ESBL or carbapenem-resistant E. coli, and K. pneumoniae, carbapenem-resistant A. baumannii complex, and P. aeruginosa. Strains were genotyped to detect ESBL and/or carbapenemase-encoding genes. Results Among blood isolates, A. baumannii complex showed more than 68% resistance for all antibiotics tested, and among Enterobacteria, E. cloacae complex showed higher resistance to carbapenems. A. baumannii complex showed a higher resistance pattern for respiratory specimens, with only amikacin having a resistance lower than 70%. Among K. pneumoniae isolates, blaTEM, blaSHV, and blaCTX were detected in 68.79%, 72.3%, and 91.9% of isolates, respectively. Among E. coli isolates, blaTEM, blaSHV, and blaCTX were detected in 20.8%, 4.53%, and 85.7% isolates, respectively. For both species, the most frequent genotype was blaCTX-M-15. Among Enterobacteriaceae, the most frequently detected carbapenemase-encoding gene was blaNDM-1 (81.5%), followed by blaOXA-232 (14.8%) and blaoxa-181(7.4%), in A. baumannii was blaOXA-24 (76%) and in P. aeruginosa, was blaIMP (25.3%), followed by blaGES and blaVIM (13.1% each). Conclusion Our study reports that NDM-1 is the most frequent carbapenemase-encoding gene in Mexico in Enterobacteriaceae with the circulation of the oxacillinase genes 181 and 232. KPC, in contrast to other countries in Latin America and the USA, is a rare occurrence. Additionally, a high circulation of ESBL blaCTX-M-15 exists in both E. coli and K. pneumoniae.